Social Cues of Safety Can Override Differences in Threat Level - Ferreira, Clara H.; Heinemans, Mirjam; Farias, Matheus; Gonçalves, Rui; Moita, Marta A. (Frontiers in Ecology and Evolution, 2022)
Animals in groups integrate social information with that directly-gathered about the environment to guide decisions regarding reproduction, foraging and defense against predatory threats. In the context of predation, usage of social information has acute fitness benefits, aiding the detection of predators, the mounting of concerted defensive responses, or allowing the inference of safety, permitting other beneficial behaviors such as foraging for food. Individual and group defense responses to predatory threats can vary in modality and vigor depending on the perceived threat level. Moreover, predation level has been shown to modulate the use of social cues about foraging sites. Whether and how different threat levels affect the use of social cues to guide defense responses, is currently unknown. We previously showed that Drosophila melanogaster display a graded decrease in freezing behavior, triggered by an inescapable visual threat, with increasing group sizes. Crucially, we identified the movement of others as a cue of safety and its cessation a cue of threat and found the group responses to be primarily guided by the safety cues, resulting in a net social buffering effect. Here, we investigated how threat level impacts the use of social cues by exposing flies individually and in groups to two threat imminences using looms of different speeds. We show that freezing responses are stronger to the faster looms regardless of social condition. However, social buffering was stronger for groups exposed to the fast looms, such that the increase in freezing caused by the higher threat was less prominent in flies tested in groups than those tested individually. Through artificial control of behavior, we created different group compositions, titrating the motion cues that were maintained across threat levels. We, found that the same level of safety motion cues had a bigger weight on the flies’ decisions when these were exposed to the higher threat, thus overriding differences in perceived threat levels. These findings shed light on the ‘safety in numbers’ effect, revealing the modulation of the saliency of social safety cues across threat intensities, a possible mechanism to regulate costly defensive responses.